WORKING WITH APPLICATION SOFTWARE (CAMTASIA STUDIO AND BANDICAM) - Jo‘rayev Voxid Tojimamatovich (Modern American Journals, 2025)
This article explores the pedagogical and technological significance of application software used for digital content creation, focusing on Camtasia Studio and Bandicam. Both tools have become integral in modern education and e-learning for producing, recording, and editing multimedia instructional materials. The paper discusses theoretical aspects of multimedia learning, methodological features of integrating video-based tools into teaching, and practical techniques for creating interactive learning resources. It also highlights comparative advantages, limitations, and the implications of using these programs in digital pedagogy. The study concludes that competence in such tools enhances both teaching quality and learners’ engagement in digital environments.
Keywords: Camtasia Studio, Bandicam, application software, digital pedagogy, multimedia learning, screen recording, educational technology, video editing, e-learning, interactive teaching.